Time to BRIC it? Internationalization of European family firms in Europe, North America and the BRIC countries - Vivien D. Procher; Diemo Urbig; Christine Volkmann (University of Wuppertal, Schumpeter School of Business and Economics, 2013)
For a sample of 1243 European companies, we analyse the link between firm type and foreign direct investment (FDI) locations. We find substantial empirical evidence that being a family firm does not only affect the overall propensity for FDI but that this effect is also specific to target regions. Overall, family firms invest more than managerial-led firms, particularly in Europe and North America. Furthermore the BRIC countries Brazil, Russia, India and China do not constitute a homogenous attractiveness cluster for FDI.
urn:nbn:de:hbz:468-20130612-112644-1
Keywords: D21; F23; L22; 330; Foreign direct investment; family firms; BRIC